Pious Imperialism : Spanish Rule and the Cult of Saints in Mexico City - Conover, Cornelius Burroughs, 1972- (Book collections on Project MUSE., 2019)
"This book analyzes Spanish rule and Catholic practice from the consolidation of Spanish control in the Americas in the sixteenth century to the loss of these colonies in the nineteenth century by following the life and afterlife of an accidental martyr, San Felipe de Jesus. Using Mexico City-native San Felipe as the central figure, Conover tracks the global aspirations of imperial Spain in places such as Japan and Rome without losing sight of the local forces affecting Catholicism. He demonstrates the ways Spanish religious attitudes motivated territorial expansion and transformed Catholic worship. By promoting its favorite canonization causes, the Spanish crown turned the cult of saints into an unimpeachable platform to proclaim the Spanish empire's shared religious mission. Using Mexico City as an example, Conover also shows that the cult of saints continually refreshed the spiritual authority of the Spanish monarch and the message of loyalty of colonial peoples to a devout king. Such a political message in worship, Conover concludes, proved contentious in independent Mexico as patriots demanded that the clergy decolonize the church, thus setting the stage for the momentous conflicts of the nineteenth century in Latin American religious history"--